AGB_VM: 0.25-degree gridded annual aboveground biomass estimates in Alaska and northwestern Canada 2003-2017.. ... - Devine, Charles John (Zenodo, 2024)
Gridded 0.25-degree annual estimates of aboveground vegetation biomass (AGB) for diverse arctic and boreal ecosystems in Alaska and northwestern Canada years 2003-2017. AGB was estimated from integrated microwave vegetation optical depth (VOD) (Vegetation Optical Depth Climate Archive (VODCA) (Moesinger et al., 2020)) and optical-multispectral vegetation indices from the MODerate Resolution Imaging Spectroradiometer (MODIS) satellite remote sensing datasets. This work was conducted through NASA's Arctic and Boreal Vulnerability Experiment (ABoVE). ...